Preparation, characterization and thermal properties of Lauryl alcohol/Kaolin as novel form-stable composite phase change material for thermal energy storage in buildings - Memon, S.; Lo, T.; Shi, X.; Barbhuiya, Salim; Cui, H. (Elsevier, 2013)
This research was aimed at developing novel form-stable composite phase change material (PCM) by incorporation of Lauryl alcohol (LA) into Kaolin (KO) through vacuum impregnation. The composite PCM was characterized by using SEM and FT-IR. Thermal properties, thermal stability and reliability of the composite were determined by using DSC, TGA and thermal cycling test. Thermal performance of cement paste composite PCM panel was also evaluated. Test results showed that the maximum fraction of LA retained in KO was 24%. SEM images showed that LA was held by the porous and layered structure of KO due to the effect of capillary and surface tension forces. FT-IR results indicated that the composite PCM has good chemical stability and the interaction between LA and KO is physical. The melting temperature and latent heat of the composite PCM were measured as 19.14 C and 48.08 J/g by DSC analysis. TGA and thermal cycling test revealed that the composite PCM is thermally stable and reliable. Thermal performance test showed that the cement paste panel with composite PCM reduced the indoor temperature by 4 C. It can therefore be concluded that the prepared composite PCM is a potential candidate for thermal energy storage in buildings.